KEBAN BARAJ GÖLÜ(ELAZIĞ)'NDE YAŞAYAN AYNALI SAZAN(CYPRİNUS CARPİO LİNNAEUS, 1758)'IN ÜREME BİYOLOJİSİ - GÜÇ, GÖKÇEN (Fırat Üniveristesi, 2006)
ABSTRACTTHE REPRODUCTION BIOLOGY OF MIRROR CARP (CYPRINUS CARPIO/,11$(86/,9,1*,1.(%$1'$0/$.((/$=,öMasters ThesisGökçen GÜÇ)Ã•UDWUniversityGraduate School of Natural and Applied SciencesDepartment of Basic Aquatic Sciences2006, Page;: 49In this study, the sexual maturity, reproduction period and fecundity of mirror carp(Cyprinus carpio Linnaeus, 1758) OLYLQJLQ.HEDQ'DP/DNH(OD]Ã•Ã·were determined betweenSeptember 2004 and April 2006.The correlation between body weight - ovarium weight (r=0.95), body weight - testisweight (r=0.91 ), body length-ovarium weight (r =0.73), body length-testis weight (r=0.77)were determined. The relations of eggs number-body weight (r=0.95), egg numbers-bodylength (r=0.93), egg numbers-ovarium weight (r=0.96), egg numbers-egg diameters (r=0.76),age grup-eggs diameter (r=0.86) were determined respectively. Egg diameters ranged 0.9-1.3mm.In conclusion, it has been found that males reached sexual maturity in age group IIIwhich was average 294 mm in length and 400,41 g in weight, where as female reached in agegroups II which was average 328 mm in length and 568,06 g in weight. Their reproductionperiod was in may-july. The prohibition of fishing during this season and of youngindividuals, that have not reached sexual maturity yet, was very important to keep on C. carpiopopulation.Key Words: Mirror carp, Cyprinus carpio, reproduction period, egg production, sexualmaturity age.III
The reproduction biology of mirror carp (Cyprinus carpio linnaeus, 1758) living in Keban Dam Lake,(Elaziğ)
Keywords: Su Ürünleri